PENGARUH STRES (RENJATAN LISTRIK) TERHADAP AKTIVITAS MOTORIK MENCIT MENGGUNAKAN METODE KETAHANAN BERENANG DI UNIVERSITAS ANDALAS - Isramilda .; Zulkarnain Edward (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Stress can increase motor activity with the role of the hormones epinephrine, norepinephrine, and the sympathetic nervous system. This study aims to determine the effect of stress (electric shock) on the motor activity of mice using swimming endurance methods at Andalas University in 2019. This research is a pure experimental study with a research design is the Randomized Experimental Posttest Only Control Group Design. This research was conducted at the Pharmacology Laboratory of Andalas University, Padang in March 2019 to April 8, 2019. The population in this study was a group of male, healthy, mice (Mus musculus) mice aged 2-3 months, with an average weight of 30-40 grams. A sample of 30 was determined by the Federer Formula, divided into 3 groups which had been adapted for 1 week. Control group (K) without stress treatment, treatment group 1 (P1) with stress treatment (electric shock), and treatment group 2 (P2) with stress treatment (electric shock) and diazepam 0.26 ml. Analysis of the results using the statistical analysis of variance (ANOVA) test. Stress treatment (electric shock) in the treatment group caused motor activity in mice to increase. The results showed a significant difference between the control group (K) with the treatment group 1 (P1) with a value of p = 0.046, the control group (K) with the treatment group 2 (P2) with a value of p = 0,000, and the treatment group 1 (P1) with treatment group 2 (P2) with a value of p = 0.006. Then Ha is accepted and H0 is rejected. Based on the results of this study it can be concluded that there is an effect of stress (electric shock) on the motor activity of mice with the swimming endurance method, where stress can increase the motor activity of the mice as evidenced by the rapid sinking of mice on the swimming endurance method.